Treatment of Myocardial Infarction with Gene-modified Mesenchymal Stem Cells in a Small Molecular Hydrogel. Issue 1 (December 2017) - Wu, Zhiye; Chen, Guoqin; Zhang, Jianwu; Hua, Yongquan; Li, Jinliang; Liu, Bei; Huang, Anqing; Li, Hekai; Chen, Minsheng; Ou, Caiwen
Abstract The effect of transplanted rat mesenchymal stem cells (MSCs) can be reduced by extracellular microenvironment in myocardial infarction (MI). We tested a novel small-molecular hydrogel (SMH) on whether it could provide a scaffold for hepatocyte growth factor (HGF)-modified MSCs and alleviate ventricular remodeling while preserving cardiac function after MI. Overexpression of HGF in MSCs increased Bcl-2 and reduced Bax and caspase-3 levels in response to hypoxiain vitro . Immunocytochemistry demonstrated that cardiac troponin (cTnT), desmin and connexin 43 expression were significantly enhanced in the 5-azacytidine (5-aza) with SMH group compared with the 5-aza only groupin vitro andin vivo . Bioluminescent imaging indicated that retention and survival of transplanted cells was highest when MSCs transfected with adenovirus (ad-HGF) were injected with SMH. Heart function and structure improvement were confirmed by echocardiography and histology in the Ad-HGF-SMHs-MSCs group compared to other groups. Our study showed that: HGF alleviated cell apoptosis and promoted MSC growth. SMHs improved stem cell adhesion, survival and myocardial cell differentiation after MSC transplantation. SMHs combined with modified MSCs significantly decreased the scar area and improved cardiac function.